THE ROLE OF IMMIGRATION TOWARD THE CRIMINAL ACTS OF CORRUPTION AS ORGANIZED TRANSNATIONAL CRIME BASED ON UNTOC'S - Jayadi Al Amien; Wisnu Widayat (Polteknik Imigrasi, 2021)
The purpose of this research is to find out the juridical background in Indonesia that the Crime of Corruption is a Transnational Crime based on the United Nations Against Transnational Organized Crime (UNTOC) and the United Nations Against Corruption (UNCAC) as outlined in Law Number 7 of 2006 which is a commitment government to combat the Corruption Crime. By using the normative-empirical research method, the importance of synergy and the responsibility of agencies dealing with Corruption in collaboration with the Directorate General of Immigration in reporting decisions, requests and orders to prevent corrupt suspects from escaping outside the territory of the Republic of Indonesia as prevention is regulated in Article 91 of Law Number 6 Year 2011 concerning Immigration.